Efeitos do capim mombaça (panicum maximum cv. mombaça) e melaço em pó na silagem de leucena (leucaena leucocephala) - Viana Roberto, Claudio Henrique; Valentim, Jean Kaique; Athaíde, Antônio Augusto Rocha; Dalago, Gabriel Machado; Almeida, Guilherme Resende de; de Souza, Mauricio Gomes; Campos Anésio, Arnon Henrique; Simão, Sergio Domingos (Revista Colombiana de Investigaciones Agroindustriales, 2018)
The objective of this study was to evaluate the bromatologic quality of Leuchena (Leucaena leucocephala) silage increasing levels of powder sugarcane molasses. In addition, it was produced Leuchena silage, but with the addition of increasing levels of powder sugarcane molasses (0, 2, 4, and 6% on natural matter basis). In total, four treatments with four repetitions were evaluated using experimental cylindrical-PVC silos arranged in a completely randomized design. After 30 days, silos were opened and evaluated pH, dry matter (DM), mineral matter (MM), neutral detergent fiber (NDF), acid detergent fiber (ADF), and hemicelulose. The use of powder molasses as an additive in the ensiling of leucena presented desirable effects in the ensiled mass, promoting some improvements in the quality of the same. The results show that as the inclusion of molasses powder in silage increases, a reduction in the levels of FDA, NDF and pH occurs. Up to 4% of molasses powder in Leucena silage is indicated for best results of MM (%) and MS (%).